MicroRNAs: New Players in Multiple Myeloma - Pichiorri, Flavia; DeLuca, Luciana; AQEILAN, RAMI I. (Frontiers in Genetics, 2011)
MicroRNAs (miRNAs) are short non-coding RNAs that play critical roles in numerous cellular processes through post-transcriptional regulating functions. The aberrant role of miRNAs has been reported in a number of haematopoietic malignancies including multiple myeloma (MM). In this review we summarize the current knowledge on roles of miRNAs in the pathogenesis of MM.